Single-step selection of drug resistant Acinetobacter baylyi ADP1 mutants reveals a functional redundancy in the recruitment of multidrug efflux systems. - Anthony J Brzoska (Public Library of Science (PLoS), 2013)
Members of the genus Acinetobacter have been the focus recent attention due to both their clinical significance and application to molecular biology. The soil commensal bacterium Acinetobacter baylyi ADP1 has been proposed as a model system for molecular and genetic studies, whereas in a clinical environment, Acinetobacter spp. are of increasing importance due to their propensity to cause serious and intractable systemic infections. Clinically, a major factor in the success of Acinetobacter spp. as opportunistic pathogens can be attributed to their ability to rapidly evolve resistance to common antimicrobial compounds. Whole genome sequencing of clinical and environmental Acinetobacter spp. isolates has revealed the presence of numerous multidrug transporters within the core and accessory genomes, suggesting that efflux is an important host defense response in this genus. In this work, we used the drug-susceptible organism A. baylyi ADP1 as a model for studies into the evolution of efflux mediated resistance in genus Acinetobacter, due to the high level of conservation of efflux determinants across four diverse Acinetobacter strains, including clinical isolates. A single exposure of therapeutic concentrations of chloramphenicol to populations of A. baylyi ADP1 cells produced five individual colonies displaying multidrug resistance. The major facilitator superfamily pump craA was upregulated in one mutant strain, whereas the resistance nodulation division pump adeJ was upregulated in the remaining four. Within the adeJ upregulated population, two different levels of adeJ mRNA transcription were observed, suggesting at least three separate mutations were selected after single-step exposure to chloramphenicol. In the craA upregulated strain, a T to G substitution 12 nt upstream of the craA translation initiation codon was observed. Subsequent mRNA stability analyses using this strain revealed that the half-life of mutant craA mRNA was significantly greater than that of wild-type craA mRNA.